Muhammadiyah's 2000 Congress: Preparing for the New Millenium - Jamhari, Jamhari (Studia Islamika, 2000)
Year 2000-popularly called as new millennium era-is a year full of congress for social and political organization as a preparation for facing new challenges of the new era. Some social and political organization such as The Party of Crescent (Partai Bulan Bintang), The Struggle Party of Indonesian Democracy (Partai Demokrasi Indonesia Perjuangan), Nahdlatul Ulama (NU) and also Muhammadiyah, the second largest Islamic social organization after NU. Mubammadiyah held its 44th congress in Jakarta. Along with the congress, some organization under-bow Muhammadiyah such as its women section, Aisyiah and Nasyiatul Aiqryiab, and its youth organization lkatan Remaja Mubammadiah (IRM) also held their congress.DOI: 10.15408/sdi.v7i3.707